Multistep and Runga-Kutta Methods for Hammerstein-Fredholm-type Integral Equation (Journal of the College of Basic Education, 2026)
The aim of this paper is to study some numerical methods for solving a special type of integral equation known as the Hammerstein-Fredholm-type integral equation (HFSKIE). The study focuses on the numerical solutions obtained through the multi-step method.